Impact of NAFTA on the Preference for Meat Consumption in USA: An Inverse Demand System Approach - Krishnapillai, Sooriyakumar (International Journal of Economics and Financial Issues, 2012)
This study examines the impacts of NAFTA on meat demand and develops an inverse demand system model for meat to analyze price and scale flexibility. The inverse demand system model for meat products suggests that, in average, NAFTA had negative impact on the preference for beef consumption. The availability of low quality beef and the concern over infectious disease through the imported beef might be the reasons for this decline on the preference for beef consumption. Results show that all meats are substitutes to each other and proportionate increase in all meats reduce the price for meats. Keywords: Inverse demand system model; NAFTA; Price and Scale Flexibility JEL Classification: Q11; Q17; D12; F13